Mock modernism : an anthology of parodies, travesties, frauds, 1910-1935 - Diepeveen, Leonard, 1959- (University of Toronto Press, 2014)
In the earliest decades of the modernist movement many interpretations of it took the form of parodies. Mock Modernism is an anthology of these amusing pieces, the overwhelming majority of which have not been in print since the first decades of the twentieth century.